5 - The Dynamics of University Transformation: A Case Study in the Eastern Cape Province of South Africa - Rómulo Pinheiro; Gerald Wangenge Ouma; Pundy Pillay (Journal of Higher Education in Africa, 2012)
This article sheds light on the dynamics of the recently created Nelson Mandela Metropolitan University (NMMU) as a result of a merger between three separate institutions. A particular focus is given to NMMU’s role in the further development of the Eastern Cape Province, one of South Africa’s poorest regions. The article discusses the impact of the amalgamation pro- cess on the university’s institutional profile, strategic platform, structural features, and scope and nature of activities. The article draws upon key insights from the institutional theory of organisations and the concepts of academic core, extended periphery and structural coupling. Taking institutionalisation as a conceptual frame of reference, it points to a number of tensions and critical success factors with respect to the university’s abil- ity to respond to external demands for a stronger engagement with sur- rounding society. Path-dependencies, local champions, and support by lead- ership structures were found to be major enablers. The lack of a strong and balanced academic core and the absence of structural linkages or tight cou- pling were identified as major challenges.